PERKEMBANGAN TANAMAN TITI (Gmelina moluccana) ENAM TAHUN SETELAH PENANAMAN - Febian F. Tetelay; Lily Pelupessy; Yacob Rahayaan; Bronnie S. Serlaloy; Hein A. Nimreskossu; Rizaldy R. Tuharea (JURNAL HUTAN PULAU-PULAU KECIL, 2020)
Titi (Gmelina moluccana) is one of the native species that grow in Maluku. The information such as the growth and development of this species was still lacking. The purpose of this study was to determine the development of Titi plants at six years after planting. This research was studied lasted for six years and the measured data were plant height and diameter for six years. The method used is to analyze the development of the Titi plant based on the growth phase of the tree. The results showed that Titi plants after six years of planting had been in the growth phase of saplings or young trees and this type was species that in catagory fast growing because it almost reaches its economic cycle. These plants can be used for forest cultivation and industrial raw materials.